2006
DOI: 10.1055/s-2006-926378
|View full text |Cite
|
Sign up to set email alerts
|

Erbium(III) Triflate: A Valuable Catalyst for the Synthesis of Aldimines, Ketimines, and Enaminones

Abstract: Aldimines, ketimines, and enaminones can be obtained under erbium(III) triflate catalysis. The reaction mechanism is that typical of imine synthesis. The role of the catalyst is demonstrated for the synthesis of aromatic imines. In contrast to CeCl 3 /NaI addition to unsaturated aldehydes, which results in Michael addition, no Michael adduct was observed under erbium(III) triflate catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…The high reactivity of a-alkylidene 5-membered cyclic carbonates (aCC) towards secondary amines [39][40][41] was exploited to design two novel bis(oxocarbamate) monomers, i. e. bis(2-methyl-3-oxobutan-2-yl) piperazine-1,4-dicarboxylate (M1) and bis(2methyl-3-oxobutan-2-yl) hexane-1,6-diylbis(methylcarbamate) (M2) following the reaction illustrated in Scheme 2. [40,41,43] Scheme 1. [40,42] DMACC was then reacted with piperazine or N,N-dimethyl-1,6-hexanediamine (DMHDA) in DMF at room temperature without any catalyst to provide the corresponding bis(oxocarbamate)s. It should be noted that primary diamines are not adapted to design bis(oxo-carbamate)s as it has previously been demonstrated that primary amines led to b-hydroxy-oxazolidinones by reaction with aCC.…”
Section: Resultsmentioning
confidence: 99%
“…The high reactivity of a-alkylidene 5-membered cyclic carbonates (aCC) towards secondary amines [39][40][41] was exploited to design two novel bis(oxocarbamate) monomers, i. e. bis(2-methyl-3-oxobutan-2-yl) piperazine-1,4-dicarboxylate (M1) and bis(2methyl-3-oxobutan-2-yl) hexane-1,6-diylbis(methylcarbamate) (M2) following the reaction illustrated in Scheme 2. [40,41,43] Scheme 1. [40,42] DMACC was then reacted with piperazine or N,N-dimethyl-1,6-hexanediamine (DMHDA) in DMF at room temperature without any catalyst to provide the corresponding bis(oxocarbamate)s. It should be noted that primary diamines are not adapted to design bis(oxo-carbamate)s as it has previously been demonstrated that primary amines led to b-hydroxy-oxazolidinones by reaction with aCC.…”
Section: Resultsmentioning
confidence: 99%
“…Possible mechanism for the formation of pyrrole is shown in the Scheme 2. We presume that initially pentane-2,4-dione 2 reacts with amine 3 to form the unsaturated amino ketone 5 and tautomerised to form intermediate 6 [29,30]. DABCO reacts with phenacyl bromide 1 and forms quaternary salt 7 [31], which subsequently react with intermediate 6 and form intermediate 8.…”
Section: Resultsmentioning
confidence: 99%
“…Dalpozzo et al 15 utilizaram triflato de érbio(III) como catalisador na preparação de aldiminas, cetiminas e enaminonas. Exemplos representativos encontram-se no Esquema 3.…”
Section: Métodos De Preparaçãounclassified